Evaluasi Pengelolaan Dana Desa Didesa Banjarrejo Kecamatan Batanghari Kabupateng Lampung Timur - Gumpita, Bagaswara; Suhada, Bambang (Jurnal Manajemen DIVERSIFIKASI, 2021)
Bagaswara Gumpita. 2021. Evaluation of Village Fund Management in Banjarrejo Village, Batanghari District. Thesis. Management Study Program, Faculty of Economics and Business. Muhammadiyah Metro University. Advisors (1) Dr. Bambang Suhada, S.E., M.Si (2) Ardiansyah Japlani, S.E., M.BA., AWM ..The study was conducted to analyze financial ratios in order to assess village government performance through village income and expenditure budget for 2019 and 2020. The financial ratios used in this study are 3 namely the ratio of independence, efficiency ratio, and effectiveness ratio. This research is quantitative descriptive. Object of research is Banjarrejo Village, Batanghari Regency. The research was conducted using data from village income and expenditure budget 2019 and 2020. The results show that the performance of the Banjarrejo Village Government from this aspect independence is still so low. whereas from the effectiveness of the performance in 2019 and 2020 it has been very effective as well as the efficiency aspect which is considered to be still less efficient in 2019 and 2020.Keywords: Village Government, Village Financial Independence, Effectiveness and Efficiency